Female Speakers Benefit More Than Male Speakers From Prosodic Charisma Training—A Before-After Analysis of 12-Weeks and 4-h Courses - Niebuhr, Oliver; Tegtmeier, Silke; Schweisfurth, Tim (Frontiers in Communication, 2019)
Perceived charisma is an important success factor in professional life. However, women are worse than men in conveying physical charisma signals while at the same time having to perform better than men in order to be perceived equally charismatic. Speech prosody probably contains the most influential charisma signals. We have developed a system called “Pascal” that analyzes and assesses on objective acoustic grounds how well-speakers employ their prosodic charisma parameters. Pascal is used for charismatic-speech training in 12-weeks and 4-h courses on entrepreneurship and leadership. Comparing the prosodic-charisma scores for a total of 72 participants at the beginning and end of these two course types showed that female speakers start with significantly lower prosodic-charisma scores than male speakers. However, at the end of the 4-h course, female speakers can catch up with their male counterparts in terms of prosodic charisma. At the end of the 12-weeks courses, male speakers keep their lead, but female speakers are able to significantly reduce the prosodic charisma gap to male speakers. Since leadership and entrepreneurship are still male-dominated domains, our results can be seen as an encouragement for women to attend prosodic charisma training. Furthermore, these courses require a gender-specific design as we found men to improve mainly in F0 parameters and women in duration and phonation parameters.